EFFECT OF FEED COMBINATION WITH DIFFERENT PERCENTAGE ON GROWTH AND SURVIVAL RATE OF THE GROUPER (Cromileptes altivelis) - Kathrine Yolanda; Usman M Tang; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on February 23th until March 23rd 2015 held at Brackishwater Aquaculture Development Center Jepara, Central of Java. This research aimed to know the growth and survival rate of Grouper (Cromileptes altivelis) with different combination and percentage treatment of feed. The method used in this study was an experimental method with Completely Randomized Design (CRD) with one factor and three replication there were, P1 (90% fresh trash fish ; 10% pellet), P2 (70% fresh trash fish ; 30% pellet), P3 (50% fresh trash fish ; 50% pellet). In this research were used a grouper with total length 5cm and total weight 2,5 g, were than kept in plastics tank with 30 cm diameter and 18 cm height were tied with plastic’s rope on the pipe. The results showed that different combination and percentage treatment of feed gave effects with grouper’s growth and the survival rate. The best percentage of treatment was P1 (90% fresh trash fish ; 10% pellet) with total weight 5,65 g, specific growth rate 2,34%, and the survival rate 100%.Key word: Grouper, Growth, Survival rate, Feed combination